LABIRIN EDUKATIF UNTUK PENGENALAN ANGKA 1-20 ANAK USIA 5-6 TAHUN - Yulia Agustina; Aprilia Wahyuning Fitri (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This research is motivated by the low ability of children aged 6-5 years in recognizing geometric shapes of flat shapes. This is caused by learning methods that tend to be passive, conventional, and the lack of utilization of varied educational game media. The purpose of this study is to develop learning media in the form of a squid shape game that is expected to help children in recognizing, naming, and distinguishing various shapes of flat shapes of course in a fun way. The research method used is Research and Development (R&D) with a 4D development model consisting of the Define, Design, Develop, and Disseminate stages. Data collection techniques through questionnaires and documentation. The research subjects used in the feasibility test of 2 kindergartens with 2 teachers, and the practicality test in 1 kindergarten with 3 teachers. Data collection instruments are validation sheets of media experts, material experts, teacher/user questionnaire sheets. Data analysis techniques used are validity tests, practicality tests, and feasibility tests of the squid shape game. The game validity data results were obtained based on the results of the media validation assessment by expert validation which obtained a percentage of 94% with a very valid category, material validation of 92% with a very valid category. The practicality data results were obtained based on the results of the teacher questionnaire assessment which obtained a percentage of 100% with a very practical category. The development of this game is expected to provide an alternative effective learning strategy for teachers in increasing motivation and understanding of flat geometry in children aged 5-6 years. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan anak usia  5-6 tahun dalam mengenal bentuk geometri bangun datar. Hal ini disebabkan oleh metode pembelajaran yang cenderung pasif, konvensional, dan kurangnya pemanfaatan media permainan edukatif yang variatif. Tujuan dari penelitian ini adalah untuk mengembangkan media pembelajaran berupa permainan squid shape game yang diharapkan dapat membantu anak dalam mengenal, menyebutkan, dan membedakkan berbagai macam bentuk bangun datar tentunya secara menyenangkan. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan 4D yssng terdiri dari tahap Define (Pendefinisian), Design (Perancangan), Develop (Pengembangan), dan Disseminate (Penyebaran). Teknik pengumpulan data melalui kueisioner dan dokumentasi. Subjek penelitian yang digunakan pada uji kelayakan  2 TK dengan 2 guru, dan uji kepraktisan pada 1 TK dengan 3 guru. Instrumen pengumpulan data adalah lembar validasi ahli media, ahli materi, lembar angket guru/pengguna. Teknik analisis data yang digunakan adalah uji kevalidan, uji kepraktisan, uji kelayakan permainan squid shape game. Hasil data kevalidan permainan diperoleh berdasarkan hasil penilaian validasi media oleh validasi ahli yang memperoleh persentase sebesar 94% dengan kategori sangat valid, validasi materi sebesarr 92% dengan kategori sangat valid. Hasil data kepraktisan diperoleh berdasarkan hasil penilaian angket guru yang memperoleh persentase 100% dengan kategori sangat praktis. Pengembangan permainan ini diharapkan dapat memberikan alternatif strategi pembelajaran yang efektif bagi guru dalam meningkatkan motivasi dan pemahaman geometri bangun datar pada anak usia 5-6 tahun.